Evolution and Coevolution: Dynamic Knowledge Capability Building for Catching-up in Emerging Economies. (22nd July 2016) - Dong, Xiaoying; Yu, Yan; Zhang, Na
ABSTRACT: Knowledge has always been a strategic resource for firms; however, there is a lack of research regarding how a firm's knowledge management (KM) contributes to its capability catching-up and adaptation in emerging economies. This article focuses on the knowledge capability building of Chinese private firms that were set up in the 1990s and pays particular attention to how firms with limited resources and knowledge went on to achieve remarkable success. This paper presents its analysis through a multi-level co-evolutionary lens and a case study on the Li-Ning Company. The case study depicts the macro coevolution between the changing business environment and the firm's strategic choices, as well as the micro coevolution of the organizational strategy and the KM orientations, processes, and infrastructures within the firm. The research sheds light on the dynamic capability building trajectory for the firms in emerging economies.